Sharing scientific and academic outputs from Cuban universities through a network of digital libraries - Machado Rivero, Manuel Osvaldo; Fernández Álvarez, Luis Carlos; Ciudad Ricardo, Febe Angel; Goovaerts, Marc; Leiva Mederos, Amed Abel; Meneses Placeres, Grizly; Benítez Erice, Didiosky; Rodriguez Fernandez, Rosa Margarita; Pérez Pupo, Redel; Acosta Nuñez, Nirma María; Cancino Gutierrez, Adrian Eduardo (My University, 2017)
In 2015 libraries from five Cuban universities supported by an international project sponsored by the Flemish Interuniversity Council (VLIR), started the development of digital libraries using Dspace to manage all the scientific and academic outputs stored in their collections with the aim to socialize, preserve and increase the visibility of the scientific and academic production at national and international level. This paper presents the main features of the first Cuban Digital Library Network, the characteristics of each repository and other platforms, their interoperability and the development of a national harvester system to allow the information’s search and retrieval through a single interface. At this moment all five digital libraries are full operating allowing the visibility and socialization of more than nine thousands thesis produced by students and postgraduate's programs from five Cuban universities. During 2017 academic and research’s staff will add their scientific production (journal articles, books and book’s chapter, and other scientific documents) making possible to duplicate the amount early cited. A librarian team defined a metadata set from the Dublin Core Qualified to homogenize the documents description, according to the type of documents that these digital libraries will store and with the Metadata Export Guidelines released by OpenAIRE. Cuban Ministry of High Education, following the experience of the five universities included in the consortial environment it decide to lead a national project to expand this experience to the rest of Cuban universities (more than 21). The interoperability of more than 20 digital libraries will allow the genesis and management in 2018 of the bigger digital collection available in Cuba, including scientific and academic and also other digital collections stored in our libraries. Also a national catalog will be available with the information about all printed collection stored in Cuban universities.
Keywords: Digital Libraries; Digital Repositories; Digital Collections; Libraries; Cuban Ministry of High Education; Bibliotecas; Repositorios Digitales; Colecciones Digitales; Bibliotecas Digitales